The Role of Farmer Group in Empowering the Household Economy of Farmers in the Archipelagic Area - Fredy H. Louhenapessy; Sherly Ferdinandus; Hermi Oppier; Djufri R. Pattilouw; Siti Aminah Silawane (Budapest International Research and Critics University, 2022)
Farmer groups have an important role in the economic empowerment of the group members. This is based on the view that, in general, the farmer group members are still entangled by various obstacles so that efforts to develop their farming businesses are often not optimal and ultimately affect the level of welfare of their own households. This research was done in a quantitative method with a case study approach studying Wijaya Farmer Group in Waiheru village, Ambon City. This research location was selected because Waiheru village was one of the largest vegetable producing or supplying areas in Ambon City. There were 20 key informants participated from a total of 40 members of Wijaya Farmer Group. The data was analyzed following stages proposed by Moustakes (1994). The results show that the income of Wijaya Farmer Group from the vegetable production was still relatively high at IDR 19,800,000 per year with an average annual income of IDR 64,223,500. Meanwhile, Wijaya Farmer Group was in the ‘fairly playing a role’ category in empowering the group members’ household economy. In addition, the strategies applied for the development of farmer groups included developing the creativity of farmer group members and the access to capital.